2020
DOI: 10.1002/1878-0261.12829
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RUNX1T1 as a potential epigenetic modifier in small‐cell lung cancer

Abstract: Small cell lung cancer (SCLC) can be sub-grouped into common 'pure' and rare 'combined' SCLC (c-SCLC). c-SCLC features a mixed tumor histology of both SCLC and non-small cell lung cancer (NSCLC). We performed targeted exon sequencing on 90 SCLC patients, including two with c-SCLC, and discovered RUNX1T1 amplification specific to small cell tumors of both c-SCLC patients, but in only 2 of 88 'pure' SCLC patients. RUNX1T1 was first identified in the fusion transcript AML1/ETO, which occurs in 12%-15% of acute my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…Studies have shown that the upregulation of RUNX1T1 can inhibit the proliferation, migration, and invasion of ovarian cancer [ 34 ]. Another study found that RUNX1T1 is highly expressed in non-small cell lung cancer through in situ hybridization [ 35 ]. Further research is needed to determine the role of this gene in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the upregulation of RUNX1T1 can inhibit the proliferation, migration, and invasion of ovarian cancer [ 34 ]. Another study found that RUNX1T1 is highly expressed in non-small cell lung cancer through in situ hybridization [ 35 ]. Further research is needed to determine the role of this gene in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…NHR3, containing a putative amphipathic helix, features in the interaction of A-kinase anchor proteins with RIIα and functions by partially binding to co-repressors [ 13 ]. The NHR4 domain, also regarded as a myeloid-Nervy-DEAF1 homology domain (MYND), exhibits two zinc structures at the C terminal, which assist in the combination of RUNX1T1 with the nuclear core repressor (N-CoR) and DNMTs to further recruit HDACs and form a co-repressive compound [ 14 ]. After the binding of the CRD with mSin3A and effective recruitment of HDACs, histone is methylated to induce a closer bind with DNA, which tightens the spatial structure of the chromosome and makes it difficult for transcription to be triggered.…”
Section: Runx1t1 Gene and Protein Structurementioning
confidence: 99%
“…Even though RUNX1T1 is downregulated in most cases of carcinogenesis, its upregulation has also been revealed in research on small cell lung cancer (SCLC) and bladder cancer [ 14 , 52 ]. By binding to the promoter of CDKN1A, RUNX1T1 inhibits histone acetylation, which leads to E2F upregulation and carcinogenesis acceleration, an expected modulation accompanying the loss of tumor-repressor RB1 in SCLC [ 14 ].…”
Section: Runx1t1 and Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RUNX1T1 also participates in the regulation of numerous biological processes, such as protein interactions [9], proliferation and differentiation of hematopoietic stem cells [11], adipocyte proliferation [12], and hippocampal neuronal differentiation [13]. Increasingly, reports indicate that RUNX1T1 is a candidate biomarker that is related to diagnosis and prognosis in various solid tumors, including pancreatic endocrine tumors, small cell lung cancer, and colorectal cancer [14][15][16]. However, the underlying functions and mechanisms of RUNX1T1 in ICIs treatment of GC are still unclear.…”
Section: Introductionmentioning
confidence: 99%